1999
DOI: 10.1002/(sici)1097-0061(199907)15:10b<987::aid-yea403>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of six novel yeast genes located on chromosome II reveals one gene essential for vegetative growth and two required for sporulation and conferring hypersensitivity to various chemicals

Abstract: A PCR‐based method for targeted gene deletion by kanMX4 module was used to construct complete deletion mutants of six individual open reading frames from chromosome II: YBR128c, YBR131w, YBR133c, YBR137w, YBR138c and YBR142w. The ORFs were deleted in two diploid strains, FY1679 and W303. Sporulation and tetrad analysis revealed that only one ORF, YBR142w, encoding a putative DEAD‐box RNA helicase, is an essential gene. A systematic phenotypic analysis of the deleted mutants was carried out. Homozygous diploids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…HSL7 and IRA1 are located only 13 kb apart from each other on chromosome II, indicating that this cosegregation could be due to linkage rather than the contribution of both genes to the trait. Although null mutations in HSL7 are associated with elongated cell morphology in other common strain backgrounds S1278B and W303 (Fujita et al 1999;Kucharczyk et al 1999), this morphological change is not observed in the S288C null mutant (Kucharczyk et al 1999), which we have confirmed using the yeast knockout collection (Giaever et al 2002). The S288C background of this evolved strain therefore makes IRA1 the more likely modifier, though the phenotype could also require both mutations.…”
Section: Phenotypic Variation Suggests Secondary Modifiers Influence supporting
confidence: 62%
“…HSL7 and IRA1 are located only 13 kb apart from each other on chromosome II, indicating that this cosegregation could be due to linkage rather than the contribution of both genes to the trait. Although null mutations in HSL7 are associated with elongated cell morphology in other common strain backgrounds S1278B and W303 (Fujita et al 1999;Kucharczyk et al 1999), this morphological change is not observed in the S288C null mutant (Kucharczyk et al 1999), which we have confirmed using the yeast knockout collection (Giaever et al 2002). The S288C background of this evolved strain therefore makes IRA1 the more likely modifier, though the phenotype could also require both mutations.…”
Section: Phenotypic Variation Suggests Secondary Modifiers Influence supporting
confidence: 62%
“…Although mon1⌬ has not been previously reported as having a role in the Cvt pathway, complementation analyses indicate that CCZ1 is allelic with CVT16, a previously uncharacterized CVT gene (10). The ccz1⌬ mutant was originally identified due to its sensitivity to caffeine, calcium, and zinc (29). It has also been shown that the strain displays a severe vacuole protein-sorting defect.…”
Section: Mon1 and Ccz1mentioning
confidence: 99%
“…It is well established that there is some variation among laboratory yeast strains of different genetic backgrounds reflected, for example, in differences between mutant or deletion phenotypes in different strains; at its extreme, genes reported as essential in a strain of one genetic background were shown to be dispensable in another (24,25). We checked whether two yeast strains, W303-1B and BY4742, widely used to obtain defined deletions of yeast open reading frames, display the same phenotype linked to the deletion of ZWF1 as described previously for other strains with presumably different genetic back- …”
Section: Ald6 and Zms1 Are Multicopy Suppressors Of Zwf1⌬ Strainmentioning
confidence: 99%